Evaluation of Syzygium jambolanum methanolic leaf extract for insulin-like properties - Lim, S.L.; Chai, J.W.; Kuppusamy, U.R. (2008)
Traditionally, the fruits and seeds of Syzygium jambolanum (Lam.) DC Family: Myrtaceae have been used to treat diabetes mellitus. Insulin is known to inhibit lipolysis induced by epinephrine as well as promote lipogenesis and glucose uptake adipocytes. The present study evaluates the insulin-like properties of S. jambolanum leaf methanolic extract through lipogenic, anti-lipolytic and glucose uptake activities. Methanolic leaf extract of S. jambolanum induced significant lipogenesis in the dose range of 0.1-10 µg mL 1 with the highest activity (114%) at 10 µg mL 1. This extract (1 µg mL 1 inhibited 29% of epinephrine (1 µM) induced lipolysis and enhanced the inhibitory effect of insulin against epinephrine induced lipolysis. This extract also inhibited (64% inhibition) of isoproterenol (1 µM) ( -adrenergic agonist) induced lipolysis. However, the extract did not enhance the antilipolytic action of propanolol ( -adrenergic antagonist). Thus, it is possible to speculate that the mode of action of this extract may involve competitive binding at -adrenergic receptor binding sites. S. jambolanum (0.1-10 µg mL 1) exerted a dose-dependant glucose uptake activity and further enhanced insulin mediated glucose uptake in primary rat adipocytes. These results confirm that S. jambolanum methanolic leaf extract has insulin-like properties and may be useful as potential therapeutic agent in the management of hyperglycemia.